THE VALIDITY AND RELIABILITY TESTING OF PUBLIC SPEAKING SKILLS QUESTIONNAIRE FOR IT STUDENTS USING SPSS - Harizahayu; Helvira Audrey Dwisastri; Friska Purba (Journal Computer and Technology, 2025)
This study aims to measure the level of relevance of public speaking knowledege among IT students in North Sumatra. The validity test was conducted to determine whether the instruments or questions in the questionnaire truly measure what they are intended to measure. The reliability test evaluates the extent to which the questionnaire can be trusted and relied upon. The research method aims to prepare a standardized questionnaire ready for use in studying students’ satisfaction with online lectures. The sample for this study consisted of 512 students who completed a Google Form. The validity test results for 77 questions indicated that 60 questions were valud with a correlation value greater than 0.25, while 17 questions were deemed invalid due to a correlation value below 0.25. The reliability test shows the Cronbach’s Alpha value > 0.60, so the instrument tested can be declared reliable or consistent.